Atypical Angelman syndrome due to a mosaic imprinting defect: Case reports and review of the literature. Issue 3 (17th February 2017) - Le Fevre, Anna; Beygo, Jasmin; Silveira, Cheryl; Kamien, Benjamin; Clayton‐Smith, Jill; Colley, Alison; Buiting, Karin; Dudding‐Byth, Tracy
Abstract : Angelman syndrome (AS) is characterized by severe intellectual disability, limited, or absent speech and a generally happy demeanor. The four known etiological mechanisms; deletions, uniparental disomy, imprinting defects, and UBE3A mutation all affect expression of the UBE3A gene at 15q11‐q13. An atypical phenotype is seen in individuals who are mosaic for a chromosome 15q11‐q13 imprinting defect on the maternal allele. These patients present with a milder phenotype, often with hyperphagia and obesity or non‐specific intellectual disability. Unlike typical AS syndrome, they can have a vocabulary up to 100 words and speak in sentences. Ataxia and seizures may not be present, and the majority of individuals do not have microcephaly. Here we review the current literature and present three individuals with atypical AS caused by a mosaic imprinting defect to demonstrate why DNA methylation analysis at the SNRPN locus needs to be considered in a broader clinical context. © 2017 Wiley Periodicals, Inc.